PENGARUH TOTAL UTANG, MODAL KERJA, DAN PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Filrisqi, Nurul Mareta; Sari, Lita Permata; Wahyuni, Ika; W, Dwi Perwitasari (Growth, 2022)
This study aimed to find out the effect of the debt, working capital, and sales variables partially, simultaneously and dominant variables that affected on the net profit variable. The research method used in this study was a quantitative descriptive method, which was a research based on data collected during systematic research regarding the facts and characteristics of the object of the tudy and then interpreted based on theory and literature related to research. Based on the results of the study, it can be concluded that the results of multiple linear regression Y = 2584.01 + 0.053 X1 - 0.006 X2 + 0.043 X3 + e. The t-test for total debt has tcount of 763 > ttable of 2.028 sig of 0.001 < 0.05. Sales has tcount of 2,445 > ttable of 2,028 sig of 0.019 < 0.05. Then the debt and sales variables partially have a significant effect on net profit. Working capital has tcount of -0.853 > -ttable of -2.028 sig of 0.399 > 0.05. So the working capital variable partially has no significant effect on net income. The value of F test showed Fcount of 29.857 > Ftable of 2.87 sig of 0.000 < 0.05, that means all independent variables have a simultaneous effect on net profit. The debt variable (X1) has the largest or dominant value compared to the other two independent variables, which is 3.763. R square of 70.8% means that it has a strong effect on Y while the remaining 29.2% is affected by other variables which are not examined.